Pola Pembinaan Muallaf Dayak di Kalimantan Tengah - Sadiani Sadiani; Akhmad Supriadi; Ahmad Fikrianor (NALAR, 2023)
This article aims to analyze the model of religious guidance for Muallaf and the various problems faced in the guidance process after religious conversion to Islam, especially among the Dayak tribal community of Central Kalimantan. This article is a descriptive qualitative study of the nature of a field study. The data was collected through purposive sampling, with interview and documentation techniques. The subjects of this research were employees at the Ministry of Religion, religious guides, and mentors of Muallaf. The research locations were conducted in three Central Kalimantan districts: Gunung Mas, Barito Utara and Murung Raya. This study found that the pattern or model of guidance for conversions to Islam in the three districts has yet to be carried out in an integrated and sustainable manner. These findings are based on the reality that there is a lack of funds, there is no concrete and valid data regarding the number of conversions to Islam, and there is no particular study or institution that provides structured, systematic and integrated guidance between religious ministries, counselors and existing religious institutions so that guidance is not carried out continuously, incidentally and ineffectively.Keywords:Muallaf;Religious conversion; Muslim Dayak; Religious Guidance